2013
DOI: 10.1097/icl.0b013e31828ef19b
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Sensitivity may Decrease in Adenoviral Epidemic Keratoconjunctivitis—A Confocal Microscopic Study

Abstract: There may be a transient decrease in the corneal sensitivity during the course of epidemic keratoconjunctivitis. Confocal microscopy can help to evaluate the changes in the cornea during this period. Future studies are needed to understand the nature of this clinical finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
5
0
5
Order By: Relevance
“…The increase in dendritic cells in the subbasal plexus is considered an important IVCM finding in EKC and herpes simplex keratitis. Öztürk et al 22 reported that herpetic keratoconjunctivitis can often be confused with adenoviral EKC due to similarities in their clinical course and common IVCM findings. In addition, a temporary reduction in corneal sensitivity has been observed following inflammatory cell activation in 74% of patients with EKC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in dendritic cells in the subbasal plexus is considered an important IVCM finding in EKC and herpes simplex keratitis. Öztürk et al 22 reported that herpetic keratoconjunctivitis can often be confused with adenoviral EKC due to similarities in their clinical course and common IVCM findings. In addition, a temporary reduction in corneal sensitivity has been observed following inflammatory cell activation in 74% of patients with EKC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a temporary reduction in corneal sensitivity has been observed following inflammatory cell activation in 74% of patients with EKC. 22…”
Section: Discussionmentioning
confidence: 99%
“…15 (%53,6) hastada tek taraflı, 13 (%46,4) hastada ise bilateral korneal tutulum olarak bildirilmiştir. 25 Çalışmamızda ise hastaların %22,2'sinde kornea tutulumu görüldü. Kornea tutulumu izlenen 16 hastanın %62,5 (10 olgu)'i erkek olup, 11 (%68,8)'inde bilateral ve 5 (%31,3)'inde sağ göz tutulumu izlendi.…”
Section: Discussionunclassified
“…7,8,9,10 Literatürde yayınlanmış olgu sunumlarında bizim olgularımızda da olduğu gibi EKK ile takip edilen hastalarda bazal epitel ve ön stroma düzeyinde yoğun inflamatuvar hücre infiltrasyonu ve dendritik hücrelerin varlığı saptanmıştır. 11,12,13,14 Korneada tutulum alanlarında yoğunlaşmış ve EKK için karakteristik olan dendritik hücreler doğal immün yanıtın aktivasyonuna işaret etmektedir. Dosso ve ark.…”
Section: Discussionunclassified